Analisis Pengaruh Model Group Investigation Terhadap Kemampuan Berpikir Historis dalam Pembelajaran Sejarah Indonesia - Nugroho, Muhammad Wahyu Adi; Putra, Arif Permana; Fadillah, Mohammad Ali (Jurnal Paedagogy, 2023)
This study aims to analyze the effect of the group investigation learning model on students' ability to think historically in Indonesian history learning. This research method used a quasi-experimental with a quantitative approach by taking the sample of this study through a non-probability sampling technique, namely students of class XI SMAN 3 Tangerang Regency. The research instrument used tests and data analysis techniques with inferential statistics and t-tests. The results of this study indicated that testing the t-test hypothesis on one side using the polled variant, the results obtained were t-test 3.70, while t-table 1.67. The statistical statement "3.7> 1.67," with a probability of error = 0.05, showed that the ability to think historically using the group investigation learning model was higher than the discovery learning model. The mean score for the posttest session for the experimental group = was 77.86, and for the control group = 66.50 indicated that the experimental group was 11.36 higher than the control group. So, the group investigation learning model can improve students' historical thinking skills in learning Indonesian history.